2000
DOI: 10.1055/s-2000-9640
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis and Catecholamine Support are the Major Risk Factors for Critical Illness Polyneuropathy after Open Heart Surgery1

Abstract: Although biventricular repair for pulmonary atresia and intact ventricular septum proved to attain a satisfactory long-term result, it failed to resolve right heart dysfunction. Postoperative arrhythmia was prone to precipitate progressive dilatation of the right atrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 19 publications
0
26
0
4
Order By: Relevance
“…In the absence of high‐grade tricuspid regurgitation (TR) this lesion leads to a hypoplastic right ventricle (RV), which may preclude a biventricular circulation after birth1, 4, 5. Even if biventricular repair can be achieved postnatally, RV function may remain abnormal and the potential of postnatal RV growth is limited6, 7. Therefore, the goal of fetal pulmonary valvuloplasty is to stimulate and promote prenatal RV growth in order to avoid significant RV hypoplasia at birth.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of high‐grade tricuspid regurgitation (TR) this lesion leads to a hypoplastic right ventricle (RV), which may preclude a biventricular circulation after birth1, 4, 5. Even if biventricular repair can be achieved postnatally, RV function may remain abnormal and the potential of postnatal RV growth is limited6, 7. Therefore, the goal of fetal pulmonary valvuloplasty is to stimulate and promote prenatal RV growth in order to avoid significant RV hypoplasia at birth.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of CINMA to prolonged mechanical ventilation has been studied in 10 cohorts of ICU patients [54,56,[65][66][67][68][69][70][71][72]. Four studies have shown an association between CINMA and an increased duration of weaning or weaning failure [49,67,70,71].…”
Section: Peripheral Dysfunctionmentioning
confidence: 99%
“…Eleven out of the 29 (38%) 25,28,29,32,[36][37][38][39][40][41][42] observational studies were graded of low quality, 17 out of 29 (59%) 12,[14][15][16]20,24,26,27,30,[43][44][45][46][47][48][49][50] as medium and one (3%) 51 as high quality. There were four RCTs included; two studies were deemed of low risk, 22,23 one unclear risk 8 and one with high risk 31 of bias.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%